MATH AND MATE IN JAVANESE CULTURE: ETHNOMATHEMATICS STUDY - Utami, Niken Wahyu; Sayuti, Suminto A; Jailani, Jailani (Journal on Mathematics Education, 2018)
A Mate in Javanese culture needs to pay attention to weton of the two brides, to predict the fate of their marriage. This study aims to reveal the numerical value, ethnomathematical of a mate in Javanese culture. The method of this research is a qualitative method. In data collection and analysis we followed the literature recommendations for educational research in ethnomathematics to utilize different qualitative research tools. We interview three informants to collect the data and make ethnographic notes. The technique of data analysis is domains analysis, taxonomy analysis, component analysis, and theme analysis of Javanese Primbon. We proposed numerical value such remainder theorems in formal mathematics attributed a mate in Javanese culture.